2006
DOI: 10.1203/01.pdr.0000246226.89215.a6
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic-Inducible Nitric Oxide Synthase in the Ischemic Developing Human Brain

Abstract: Variability in the expression of apoptotic and inflammatory mediators with time after an ischemic insult and their role in the expansion of cerebral infarcts are still controversial. This study examines DNA degradation and the expression of activated caspase-3 and iNOS, inducible nitric oxide (iNOS) in the human developing brain. Autopsy specimens from children with a neuropathologic diagnosis of focal ischemic infarct were included in the study. The specimens were classified based on the clinical history as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…Core of chronic infarcts (wks-mo/y) were basically cavities with surrounding astrogliosis and in some cases persistent histiocytes. Normal brain parenchyma directly adjacent to the ischemic "core" is the "penumbra" as defined previously (10). None of the age-matched control brain sections showed any pathologic changes.…”
Section: Methodsmentioning
confidence: 88%
See 4 more Smart Citations
“…Core of chronic infarcts (wks-mo/y) were basically cavities with surrounding astrogliosis and in some cases persistent histiocytes. Normal brain parenchyma directly adjacent to the ischemic "core" is the "penumbra" as defined previously (10). None of the age-matched control brain sections showed any pathologic changes.…”
Section: Methodsmentioning
confidence: 88%
“…The neuronal expression of XIAP in human ischemic brain, we found, is in keeping with previous studies showing XIAP in cerebral neurons of neonatal mice (12), adult rat (17), and mice (18) brain after ischemic injury. We have previously shown that apoptotic cell death persists for several days in the ischemic human developing brain and that the number of caspase-3 positive cells significantly decreased in the penumbra of subacute compared with acute infarcts (10). Increasing XIAP expression in the penumbra of subacute infarcts may play a role in inhibiting both caspase-dependent and -independent apoptosis in ischemic developing brain (5)(6)10).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations